Adverse cardiovascular events associated with biodegradable polymer drug-eluting stents and durable polymer everolimus-eluting stents: A systematic review and meta-analysis of 10 randomized controlled trials. Issue 28 (July 2017) - Bundhun, Pravesh Kumar; Janoo, Girish; Yanamala, Chandra Mouli; Huang, Feng
Abstract: Background: Controversies have been observed among network meta-analyses comparing biodegradable polymer drug-eluting stents (BP-DES) with durable polymer drug-eluting stents (DP-DES). We aimed to compare the adverse cardiovascular events associated with BP-DES and durable polymer everolimus-eluting stents (DP-EES) using a large number of patients obtained from randomized controlled trials (RCTs). Methods: Electronic databases were searched for randomized trials comparing BP-DES with DP-EES. Adverse cardiovascular outcomes observed between 6 months and 3 years were considered as the clinical endpoints in this analysis. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated and the pooled analyses were performed with RevMan 5.3 software. All authors had full access to the data, and they have read and agreed to the manuscript as written. Results: Ten trials involving a total number of 13, 218 patients (7451 patients treated by BP-DES and 5767 patients treated by DP-EES) were included. No significant difference was observed when analyzing mortality and myocardial infarction between BP-DES and DP-EES with OR 1.08, 95% CI 0.87–1.34, P = .47 and OR 1.04, 95% CI 0.84–1.28, P = .72 respectively. Target vessel revascularization, target lesion revascularization, major adverse cardiac events, and stroke were also not significantly different with OR 1.11, 95% CI 0.92–1.33, P = .28; OR 1.11, 95% CI 0.94–1.33, P = .22; OR 1.12, 95% CI 0.99–1.27; P = .07; and OR 1.13, 95% CI 0.69–1.84; P = .62 respectively. In addition, total stent thrombosis (ST) was similarly reported between BP-DES and DP-EES with OR 0.85, 95% CI 0.59–1.21; P = .37. However, even if BP-DES were associated with a higher rate of definite ST with OR 1.69, 95% CI 0.92–3.08, P = .09 and DP-EES were associated with a higher rate of probable ST with OR 0.67, 95% CI 0.38–1.17, P = .16, these results were not statistically significant. Conclusions: Between 6 months and 3 years, BP-DES were similar in terms of cardiovascular outcomes compared to DP-EES. However, further long-term follow-up research is recommended.